Hubungan Kenaikan Suhu Tubuh dengan Defisit Neurologis Pada Pasien Stroke Iskemik - Putri, Indah Riyansa, Dr. Iwan Setiawan, Sp.S (2017)
Stroke is a brain disease with clinical manifestations of neurological disorders in local and global function that can lead to sudden neurologic deficits and is the result of ischemia or hemorrhage circulation of the brain's neurons. Factors causing neurological deficits including the rise in body temperature. This study aims to investigate the relationship rise in body temperature with neurological deficits in patients with ischemic stroke this study included non-experimental observational analytic with cross sectional approach, sampling with purposive sampling a number of 42 patients with ischemic stroke. Data obtained from secondary data and primary data by questionnaire. Mengggunakan statistitk Analysis Chi-Square Test. Results of the study were statistically with Chi-Square test showed that there was no significant relationship between the increase in body temperature with neurological deficits in patients with ischemic stroke with the value ρ = 0.291 (ρ> 0.05) and the value x2 = 2,472. The conclusion from this study that there was no relationship with the body temperature rises neurological deficits in patients with ischemic stroke.